Situation Report: Czechoslovakia, 25 March 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Czechoslovakia's Proposal for a "Zone of Confidence" Milos Jakes's Visit to the GDR / by Jan Obrman The Value of Economic Experiment in Czechoslovakia The Czechoslovak Economy from the Communist Takeover to Perestroika The Party's Private Army / by Jan Obrman John Lennon and Pacificism [Pacifism] in Czechoslovakia / by Jan Obrman The Institutions of "Scientific Atheism" / by Jozef Spetko The New Literary Periodical Kmen / by Antonin Kratochvil